PROSES PENEGAKAN HUKUM TERHADAP KASUS PENGANIAYAAN MARIO DANDY KEPADA DAVID OZORA - Openg, Crameraldo Anugerah Putra; Wage, Guido Tobhi; Araujo, Rojalia Rica De; Geong, Mario Pietro Kurniawan; Wahon, Ernesta Uba (LPPM STIH Awang Long, 2023)
Efforts to ensure that regulations in society function properly as law enforcement. Law enforcement officers are expected to be able to carry out their obligations to enforce the law against perpetrators, especially those who carry out law enforcement. This journal discusses two issues. First, how does law enforcement handle the perpetrator? Second, how society acts regarding the Mario Dandy case which involves thinking. The author uses normative research methods by collecting data from legal materials which contain various normative legal rules. The data they obtain and process comes from library sources. The author searched for previous literature by reading articles, books, and websites related to this subject. The research results show that Mario Dandy, the perpetrator of the abuse in this case, was charged with Article 355 paragraph (1) subsidiary 354 paragraph (1) of the Criminal Code, Article 353 paragraph (2) of the Criminal Code, and/or 76 C in conjunction with 80 of the Child Protection Law. This puts him in danger of a maximum prison sentence of 12 years. Because of this, law enforcement responded to Mario Dandy with great anger and hoped that this case would be resolved legally and not end peacefully. They hope this incident will be a lesson for teenagers and parents about education and payments. pay attention to the actions of the children. As a result, law enforcement that can provide justice and truth to legal officers is needed to make people more careful and teach wisdom to their children.